FROM DIGITAL INFRASTRUCTURE TO EMPLOYEE PERFORMANCE IN PUBLIC SECTOR TRANSFORMATION - Yunus, Asraf; Qadri, Muhammad Nuzul; Hakim, Abdul (Journal of Business Studies and Management Review, 2026)
Digital transformation in public sector organizations requires not only technological adoption but also employees’ active engagement in digitally mediated work. This study examines the effects of technological infrastructure on digital leadership, digital readiness, digital work engagement, and employee performance in public sector organizations. A quantitative explanatory design was employed using survey data from 182 public sector employees. The data were analyzed using partial least squares structural equation modeling with SmartPLS 4. The findings reveal that technological infrastructure has a strong positive effect on digital leadership, digital readiness, and digital work engagement. However, digital leadership and digital readiness do not directly improve employee performance. Digital work engagement emerges as the strongest predictor of employee performance and the only significant mediator linking technological infrastructure to employee performance. These findings indicate that technological infrastructure generates performance value when it fosters employees’ enthusiasm, focus, dedication, and active involvement in digital work. The study contributes to public sector digital transformation literature by positioning digital work engagement as the central behavioral mechanism through which technological infrastructure is converted into employee performance. Practically, public organizations should move beyond technology provision and design digital work environments that enhance employees’ engagement with digital systems